Menimbang Prospek Komunikasi Individual HAM: Politik Hukum dan Implikasi Potensial Bagi Indonesia - Abdul Munif Ashri; Heribertus Jaka Triyana (Badan Strategi Kebijakan Hukum, 2024)
The individual communications procedure is a vital mechanism in international human rights law that enables victims to seek remedies when domestic legal venues have been exhausted or failed to deliver justice. Although Indonesia has acceded to almost all core international human rights treaties, its individual communications procedures have yet to be accepted. This study investigates the Indonesian Government's human rights legal policy toward individual communications procedures acceptance through the ratification/accession of the ICCPR First Optional Protocol and ICESCR Optional Protocol, as well as analyzes the potential implications of such acceptance. This study utilizes a normative legal methodology coupled with interdisciplinary and conceptual approaches. In addition to analyzing legal materials, interviews were conducted with scholars, NGO activist, victim, and former Commissioner of Indonesia's National Human Rights Commission to deepen the analysis. The findings reveal the Government's lack of political will to accept individual communications procedures due to a tendency to avoid adjudicatory human rights accountability mechanisms and the avoidance of possible compliance costs, such as financial, reputational, and political burdens. Furthermore, this study demonstrates that these procedures' acceptance has potential implications for opening access to justice for victims, providing strategic litigation channels, and facilitating interaction between treaty bodies and the national judiciary regarding the development of interpretations of human rights through judicial dialogue. The Government should consider ratifying/acceding the ICCPR and ICESCR Optional Protocols to strengthen the domestic human rights protection infrastructure and enhance its reputation as a promoter of human rights.